2023
DOI: 10.1371/journal.pone.0277804
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative temporal vegetation indices from unoccupied aerial systems allow maize (Zea mays L.) hybrid yield to be estimated across environments with fewer flights

Abstract: Unoccupied aerial systems (UAS) based high throughput phenotyping studies require further investigation to combine different environments and planting times into one model. Here 100 elite breeding hybrids of maize (Zea mays L.) were evaluated in two environment trials–one with optimal planting and irrigation (IHOT), and one dryland with delayed planting (DHOT). RGB (Red-Green-Blue) based canopy height measurement (CHM) and vegetation indices (VIs) were estimated from a UAS platform. Time series and cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…They found that the RF model performed the best for yield prediction, and that the ML models generally performed better than the stepwise regression model. Chatterjee et al [87] used temporally accumulated VIs as features fed into ML models and found that normalized difference type VIs produced the best model performance and that the flowering growth stage was the best time to acquire imagery. Some yield prediction works explored the prediction power of different types and combinations of features.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the RF model performed the best for yield prediction, and that the ML models generally performed better than the stepwise regression model. Chatterjee et al [87] used temporally accumulated VIs as features fed into ML models and found that normalized difference type VIs produced the best model performance and that the flowering growth stage was the best time to acquire imagery. Some yield prediction works explored the prediction power of different types and combinations of features.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several attempts have been successfully applied for using temporal phenotype (e.g. temporal plant height and NDVI) in maize (Han et al ., 2019; Wang et al ., 2019, 2021; Anderson et al ., 2020; Tirado et al ., 2020; Adak et al ., 2021b, 2023b; Oehme et al ., 2022; Rodene et al ., 2022; Chatterjee et al ., 2023), sorghum (Miao et al ., 2020), cotton (Pauli et al ., 2016), and rice (Sun et al ., 2022). However, several important limitations exist when examining temporal phenotypes and incorporating these into QTL or genomic association mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Other VIs like the normalized green red difference index have been associated with water use efficiency ( Yang et al . 2020 ) and also are recognized as an important predictor of GY in maize ( Chatterjee et al . 2023 ).…”
Section: Discussionmentioning
confidence: 99%